Re(I) Complexes as Backbone Substituents and Cross-Linking Agents for Hybrid Luminescent Polysiloxanes and Silicone Rubbers - Egor M. Baranovskii; Victoria V. Khistiaeva; Konstantin V. Deriabin; Stanislav K. Petrovskii; Igor O. Koshevoy; Ilya E. Kolesnikov; Elena V. Grachova; Regina M. Islamova (Molecules, 2021)
This study focuses on the synthesis of hybrid luminescent polysiloxanes and silicone rubbers grafted by organometallic rhenium(I) complexes using Cu(I)-catalyzed azido-alkyne cycloaddition (CuAAC). The design of the rhenium(I) complexes includes using a diimine ligand to create an MLCT luminescent center and the introduction of a triple C≡C bond on the periphery of the ligand environment to provide click-reaction capability. Poly(3-azidopropylmethylsiloxane-co-dimethylsiloxane) (N3-PDMS) was synthesized for incorporation of azide function in polysiloxane chain. [Re(CO)3(MeCN)(5-(4-ethynylphenyl)-2,2′-bipyridine)]OTf (Re1) luminescent complex was used to prepare a luminescent copolymer with N3-PDMS (Re1-PDMS), while [Re(CO)3Cl(5,5′-diethynyl-2,2′-bipyridine)] (Re2) was used as a luminescent cross-linking agent of N3-PDMS to obtain luminescent silicone rubber (Re2-PDMS). The examination of photophysical properties of the hybrid polymer materials obtained show that emission profile of Re(I) moiety remains unchanged and metallocenter allows to control the creation of polysiloxane-based materials with specified properties.